Management of antithrombotic treatment and bleeding disorders in patients requiring venous access devices: A systematic review and a GAVeCeLT consensus statement. Issue 4 (July 2022) - Annetta, Maria Giuseppina; Bertoglio, Sergio; Biffi, Roberto; Brescia, Fabrizio; Giarretta, Igor; Greca, Antonio La; Panocchia, Nicola; Passaro, Giovanna; Perna, Francesco; Pinelli, Fulvio; Pittiruti, Mauro; Prisco, Domenico; et al.
Insertion of venous access devices (VAD) is usually considered a procedure with low risk of bleeding. Nonetheless, insertion of some devices is invasive enough to be associated with bleeding, especially in patients with previous coagulopathy or in treatment with antithrombotic drugs for cardiovascular disease. The current practices of platelet/plasma transfusion in coagulopathic patients and of temporary suspension of the antithrombotic treatment before VAD insertion are based on local policies and are often inadequately supported by evidence, since many of the clinical studies on this topic are not recent and are not of high quality. Furthermore, the protocols of antithrombotic treatment have changed during the last decade, after the introduction of new oral anticoagulant drugs. Though some guidelines address some of these issues in relation with specific procedures (port insertion, etc.), no evidence-based document covering all the aspects of this clinical problem is currently available. Thus, the Italian Group of Venous Access Devices (GAVeCeLT) has decided to develop a consensus on the management of antithrombotic treatment and bleeding disorders in patients requiring VADs. After a systematic review of the available evidence, the panel of the consensus (which included vascular access specialists, surgeons, intensivists, anesthetists, cardiologists, vascular medicine experts, nephrologists, infective disease specialists, and thrombotic disease specialists) has structured the final recommendations as detailed answers to three sets of questions: (1) which is an appropriate classification of VAD-related procedures based on the specific bleeding risk? (2) Which is the appropriate management of the patient with bleeding disorders candidate to VAD insertion/removal? (3) Which is the appropriate management of the patient on antithrombotic treatment candidate to VAD insertion/removal? Only statements reaching a complete agreement were included in the final recommendations, and all recommendations were offered in a clear and synthetic list, so to be easily translated into clinical practice.